A New Coupled Ocean‐Waves‐Atmosphere Model Designed for Tropical Storm Studies: Example of Tropical Cyclone Bejisa (2013–2014) in the South‐West Indian Ocean. (23rd March 2018) - Pianezze, J.; Barthe, C.; Bielli, S.; Tulet, P.; Jullien, S.; Cambon, G.; Bousquet, O.; Claeys, M.; Cordier, E.
Abstract: Ocean‐Waves‐Atmosphere (OWA) exchanges are not well represented in current Numerical Weather Prediction (NWP) systems, which can lead to large uncertainties in tropical cyclone track and intensity forecasts. In order to explore and better understand the impact of OWA interactions on tropical cyclone modeling, a fully coupled OWA system based on the atmospheric model Meso‐NH, the oceanic model CROCO, and the wave model WW3 and called MSWC was designed and applied to the case of tropical cyclone Bejisa (2013–2014). The fully coupled OWA simulation shows good agreement with the literature and available observations. In particular, simulated significant wave height is within 30 cm of measurements made with buoys and altimeters. Short‐term (< 2 days) sensitivity experiments used to highlight the effect of oceanic waves coupling show limited impact on the track, the intensity evolution, and the turbulent surface fluxes of the tropical cyclone. However, it is also shown that using a fully coupled OWA system is essential to obtain consistent sea salt emissions. Spatial and temporal coherence of the sea state with the 10 m wind speed are necessary to produce sea salt aerosol emissions in the right place (in the eyewall of the tropical cyclone) and with the right size distribution, which is critical for cloud microphysics. Key Points: A new coupled Ocean‐Waves‐Atmosphere system (MSWC) is presented in this paper MSWC successfully simulates air‐sea processes under a tropical cyclone at kilometer resolution MSWC shows the importance of using a fully coupled system to have consistent sea salt aerosol fluxes and concentration